Answered

Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Given: F(x) = x + 2 and G(x) = 3x + 5

(F + G) (x) =


Sagot :

f(x) = x + 2
g(x) = 3x + 5

(f + g)(x) = (x + 2) + (3x + 5)
(f + g)(x) = (x + 3x) + (2 + 5)
(f + g)(x) = 4x + 7
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.